Psychiatric Disorders Associated with Deliberate Self-Harm: A Study of Frequency and Suicidal Intent at Rajshahi Medical College Hospital (Community Based Medical Journal, 2026)
Deliberate self-harm (DSH) is a significant public health concern, often associated with psychiatric disorders and varying degrees of suicidal intent. Understanding the psychiatric profiles and suicidal intent among DSH patients can aid in early intervention and prevention strategies. A prospective, cross-sectional study was conducted to determine the frequency of psychiatric disorders, deliberate self-harm and suicidal intent among admitted patients in the Department of Psychiatry, Rajshahi Medical College Hospital, Rajshahi, Bangladesh, from May 2024 to April 2025. The study involved 132 patients who were purposively selected. Data were collected through structured interviews and clinical evaluations using standardized tools. Psychiatric diagnoses were made following ICD-10 criteria, and suicidal intent was assessed using the Beck Suicidal Intent Scale (SIS). Among 132 patients, depressive disorders (42.4%) were most prevalent, followed by substance use (23.5%) and anxiety disorders (15.9%). High suicidal intent was found in 38.6% cases, moderate in 45.5%, and low in 15.9%. Females showed higher depression rates (p=0.003), while males had more substance use disorders (p=0.012). Pesticide poisoning (62.1%) correlated with high intent (p=0.004). Age and socioeconomic status significantly influenced psychiatric profiles (p